2015
DOI: 10.1177/0193945915609902
|View full text |Cite
|
Sign up to set email alerts
|

Retention of African American Women in a Lifestyle Physical Activity Program

Abstract: Using a cohort of African American women enrolled in a physical activity program, the purpose of the paper is to examine how well individual characteristics, neighborhood characteristics and intervention participation predict study retention and staff level of effort needed for retention. Secondary data analysis was conducted from a randomized clinical trial. Participants were 40–65 years without major signs/symptoms of cardiovascular disease. Assessments were conducted at community sites in/bordering African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Several researchers have published on reasons and motivators of adults to continue in exercise trials. For example, Buchholz and colleagues found that women with more hardships and perceived poor health took more reminder phone calls to encourage their continued participation [33]. In a study of motivators to join and stay with an exercise trial, Viljoen and Christie found that participant motivators changed over time.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have published on reasons and motivators of adults to continue in exercise trials. For example, Buchholz and colleagues found that women with more hardships and perceived poor health took more reminder phone calls to encourage their continued participation [33]. In a study of motivators to join and stay with an exercise trial, Viljoen and Christie found that participant motivators changed over time.…”
Section: Discussionmentioning
confidence: 99%
“…25 Among retention strategies described earlier was $40 for completing each study assessment (baseline, 24 weeks, and 48 weeks) and a pedometer given to participants at study completion. 26 All participants provided informed written consent. A total of 288 women were screened eligible for the study and are included in these analyses.…”
Section: Setting and Samplementioning
confidence: 99%
“…18-20 Several PA interventions have relied upon popular theories to promote PA among African American women. 21-25 Each study acknowledged the benefits of utilizing a theoretical framework to drive the development and deployment of their intervention to promote and increase PA. However, there is further need to ameliorate theoretical approaches.…”
Section: Introductionmentioning
confidence: 99%